Can ESG performance contribute to a reduction in banks’ nonperforming loans? evidence from emerging countries banks - Hussain, Suman Najam; Ali, Rosalan; Johari, Jalila (Elite Scientific Forum, 2024)
Banks play a crucial role in fostering financial stability, and understanding how ESG performance can impact loan quality is vital, particularly in economies with varying regulatory frameworks. Using a quantitative research approach, this study examines the relationship between nonperforming loans (NPLs) and environmental, social, and governance (ESG) performance in banks within emerging markets banks. Utilizing data from banks in these regions, we find a negative correlation between a bank's ESG score and its level of NPLs. Additionally, we observe that strong performance across all three ESG pillars- Environmental, Social, and Governance—reduces the NPL ratio. Our findings suggest an improved ESG approach bolstering financial stability by indicating that higher ESG performance improves loan quality in emerging market banks and thus reduces NPLs.